ICT and Reflective Practice integration; A Constructivists Approach in Teacher Preparation at Primary Teachers Colleges in South Eastern Uganda - Gusango, Emmanuel; Maani, John; Ssetumba, John (American Journal of Education and Practice, 2021)
Purpose: The purpose of this study was to explore the ICT and reflective practice integration in teacher preparation at Primary Teachers Colleges and to establish whether these practices were among the constructivist approaches being used to teach students. Methodology: This phenomenological study explored the lived experiences of tutors and students in light of constructivists' teaching. It involved 3 PTCs and 15 participants who were purposively sampled. This study used a qualitative research design. Data was gathered using in-depth multiple interviews and analyzed following Moustakas (1994) procedure. Findings: Data analysis and results revealed that tutor"˜s continue to rely on traditional approaches in both instruction and supervision of school practice. The colleges are in a nascent stage in the integration of ICT and reflective practice in education being accustomed to traditional instructional practices and lack of motivation and knowledge among tutors to adopt ICT in teaching. Unique Contribution to Theory, Practice and Policy: This research study adds to the body of knowledge suggesting ways in which constructivists' teaching supports teaching effectiveness and promotes students' learning amplifying the need for ICT and reflective practice integration in instruction. The study recommends establishing and setting up Reflective Practice Laboratories in Primary Teachers Colleges for tutors and students induction on several constructivists' practices that include systematic reflection, clinical supervision, use and integration of ICT and other interventions in a proper and professional setting